The Average Collection Period, The Inventory Turnover Period, and The Average Inventory Period: Statistical Relations and Interpretation - Samer Hamad (European Scientific Journal, ESJ, 2024)
The importance of the Cash Conversion Cycle emerges in helping to make appropriate financing decisions for different industries. Therefore, the research mainly focuses on the return on assets (ROA) issues and how it is affected by the three components of the cash conversion cycle; Average Collection Period (ACP), Average Inventory Turnover Period (ITP), and Average Payment Period (APP). Since the topic refers to the potential statistical relationship between the three components and the return on assets, the research has been organized to ascertain the validity of the answer to the research questions and hypothesis regarding which component affects more on the return on assets. The research indicates that more APPs lead to more return on assets. On the other hand, a negative relationship between ACP ITP and ROA indicates that managers can produce more value by minimizing ACP and ITP to a fair figure. In addition, the findings indicate that attention should be paid to the components of the cash conversion cycle to avoid periods of potential financial distress.